PERANCANGAN PLATFORM MARVELOUS PINRANG UNTUK EKSISTENSI PARIWISATA KABUPATEN PINRANG - Novita; Najib, Marhawati; Aris, Valentino (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
The tourism sector plays a crucial role in driving Indonesia's economy. Pinrang Regency, with its diverse natural tourist attractions, holds significant potential for tourism development. This study aims to design and develop the Marvelous Pinrang platform to enhance the tourism sector in Pinrang Regency. The platform is designed using the WordPress CMS, featuring destination information, interactive maps, media galleries, and user comments. The platform's usability was evaluated using the System Usability Scale (SUS). The results indicate a high usability score, suggesting that the platform can effectively support tourism activities in Pinrang Regency. The development of this platform is expected to increase public awareness of the tourism potential in Pinrang Regency and attract more visitors to the region. By leveraging digital technology, the Marvelous Pinrang platform provides an accessible and user-friendly solution for promoting local destinations. Furthermore, the platform serves as a tool for fostering collaboration between local governments, businesses, and communities to strengthen the tourism ecosystem in Pinrang Regency.